Bite me: Blue tails as a ‘risky-decoy’ defense tactic for lizards - Bateman, Bill; Fleming, P.; Rolek, B. (Current Zoology Editorial Office, 2014)
Many lizard species use caudal autotomy to escape entrapment. Conspicuous coloration may increase the likelihood of being attacked, but if that attack can be directed towards the autotomous tail this may ultimately increase the chances of the lizard surviving a predatory attack. We tested the hypothesis that brightly-colored tails function to divert predatory attention away from the head and body using pairs of blue-tailed and all-brown clay model lizards. Predatory bird attacks on the 24 blue-tailed models occurred sooner (P = 0.001) than attacks on the 24 all-brown models, and over 7 days blue-tailed models were attacked more often than all-brown models (P = 0.007). Blue-tailed models were, however, more frequently attacked on the tail than other parts of the body (P < 0.001), while all-brown models were more frequently attacked on the head and body (P = 0.019) which would be more likely to be fatal for a real lizard. Our results suggest that models with a blue tail were more conspicuous than all-brown models, attracting attacks sooner and more often, but that the attacks were predominantly directed at the tail. It is better for individuals to be attacked unsuccessfully many times, than successfully just once. Having a brightly-colored tail may, therefore, act as a 'risky decoy'. Despite increased conspicuousness, a blue tail increases the likelihood that the lizard would be able to effect escape through caudal autotomy rather than being grabbed by the head or body.